Improving salinity tolerance in transplanted aman rice (Oryza sativa L.) by exogenous application of proline: Proline improves salt tolerance in rice (Journal of the Bangladesh Agricultural University, 2019)
Salinity is the major factor reducing crop yield in coastal areas of Bangladesh. Proline (Pro) application with suitable crop varieties having higher yield potential could contribute to the improvement of crop production in saline areas. The main objective of this study was to investigate the mitigation of adverse effects of salinity in aman rice by exogenously applied Pro. The experiment was carried out at the farmer’s field of Batiaghata, Khulna. Characteristically, the soil was silty clay loam having pH 6.7, EC 4.6 dS m–1, CEC 23 meq/100 g soil, organic matter 0.71%. Rice (Oryza sativa L.) variety BR23 was used as plant material. The experiment was laid out in a randomized complete block design with three replications. There were different treatment combinations namely control (no Pro), 25 mM Pro at seedling stage, 25 mM Pro at vegetative stage, 25 mM Pro at seedling and vegetative stages, 50 mM Pro at seedling stage, 50 mM Pro at vegetative stage, 50 mM Pro at seedling and vegetative stages, 100 mM Pro at seedling stage, 100 mM Pro at vegetative stages, and 100 mM Pro at seedling and vegetative stages. Recommended doses of N, P, K, S and Zn fertilizers were applied to the all experimental plots. Thirty-day-old seedlings were transplanted in the experimental plots. Proline solutions were sprayed over plant leaves with the help of sprayer as per treatments. Salinity caused significant reductions in growth and yield of BR23 by decreasing plant height, number of effective tillers, panicle length, filled grains panicle-1 and 1000-grain weight. On the other hand, exogenous application of Pro showed a significant increase in growth and yield of BR23 under saline conditions. Results also revealed that growth and yield of rice did not increase proportionally with the increasing doses of Pro. Proline application resulted in significant increases in K+/Na+ and nutrient uptake by rice under salinity. The present study suggests that exogenous application of Pro confers tolerance to salinity in aman rice by increasing K+/Na+ ratio and nutrient uptake.J. Bangladesh Agril. Univ. 17(2): 194–199, June 2019